A decade of Australian reconstructive burn surgery in Nepal 2004-2014 - David G Pennington (Australasian Journal of Plastic Surgery)
Nepal is a nation with an emerging economy that traditionally has faced challenges related to terrain, weather, political instability, natural disasters and poverty. It has a very high rate of burn injury. Due to the above factors, adequate primary treatment of burns is frequently rudimentary, resulting in a significant burden of human misery in the form of chronic debilitating burn-scar contractures. For several decades, international health teams have played a significant role in relieving the burden of disease and deformity, such as cleft lip and palate and burn-scar reconstruction. The current article summarises the experience of an Australian surgical team assembled to manage problems of burn-scar contracture in Nepal over the ten-year period 2004–2014.